Identification and abundance of stink bug species (Hemíptera: Pentatomidae) in rice cultivation - Guananga Demera, Karen Stefany; Zambrano Bosquez, Juan Pablo; Recalde Luna, Sandra Lisseth (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2023)
Rice fields are excellent habitats for insects and about 20 species of pest-insects are considered economically important due to their phytophagous behavior. Among the insects that have predominated in these crops are the "rice bugs" (Hemiptera: Pentatomidae). Taking into account that it affects the yield and productivity in the rice harvest, causing empty panicles or with retarded growth and the presence of injured grains. The objective of this research is to update the inventory of the rice spike bug complex in Daule Canton, considered a site of great rice production in Ecuador. 10 rice-producing farms were selected, and the samples were collected following the methodology of Pantoja, the taxonomic identification was carried out in the Entomology Laboratory of the Ecuadorian Agency for Phytosanitary and Zoosanitary Regulation and Control (Agrocalidad). Two species of the genus Oebalus were identified, being the most abundant O. ornatus with 96.87% while O. pugnax obtained 3.13%, found in only 1 rice-producing farm.
Keywords: Genus; rice bug; hemiptera; Oebalus; phytophagous